2004
DOI: 10.1196/annals.1335.032
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis and Inflammation in Infertility

Abstract: A wealth of publications proposes that endometriosis and inflammation may have an unfavorable influence on fertility. A recent meta-analysis of assisted reproductive technologies demonstrated that, once confounding factors are controlled for, the pregnancy rate in women with endometriosis is approximately 50% of the rate of women with tubal factor infertility. Peritoneal fluid of women with endometriosis contains elevated amounts of macrophages and their secreted products, such as growth factors, cytokines, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(104 citation statements)
references
References 154 publications
(233 reference statements)
2
98
0
4
Order By: Relevance
“…Halis and Arici (2004) have reported that most of the inflammatory reactions occur at the earlier stages of the disease, when most cytokines, chemokines and growth factors are secreted into peritoneal fluid. Haney et al (1991) showed an inverse relationship between the total number of peritoneal macrophages and the extension of pelvic endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Halis and Arici (2004) have reported that most of the inflammatory reactions occur at the earlier stages of the disease, when most cytokines, chemokines and growth factors are secreted into peritoneal fluid. Haney et al (1991) showed an inverse relationship between the total number of peritoneal macrophages and the extension of pelvic endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Kerusakan tuba fallopi disebabkan karena penyakit radang panggul, endo-metriosis, dan riwayat operasi sebelumnya. 22,23 Pada penelitian ini infeksi Chlamydia trachomatisdi masa lampau merupakan faktor yang berbeda secara signifikan pada subyek dengan kerusakan tuba fallopi yang dideteksi melalui IgG Chlamydia trachomatis (p = 0,01), sedangkan endometriosis dan riwayat operasi pada penelitian ini didapat hasil yang tidak signifikan (p = 0,26 dan p = 0,27) seperti tercantum dalam tabel 2. Hal ini dapat menjadi indikasi bahwa infeksi Chlamydia trachomatis sebagai penyebab kerusakan akibat proses inflamasi pada tuba fallopi dan penanda infeksi ini sebagai prediktor terhadap kondisi tuba fallopi.…”
Section: Kondisi Tuba Fallopi Berdasar Temuan Laparoskopiunclassified
“…Another report indicates a fecundity of 0.15-0.20 per month in normal couples but 0.02-0.10 in untreated women with endometriosis and infertility [4]. Therefore in women with stage III-IV monthly probability to conceive is 2-10% vs. 15-25% in healthy couples [5].…”
Section: Endometriosis and Ivfmentioning
confidence: 99%